Development of Interactive Islamic Education Learning Media Using Artificial Intelligence and ChatGPT - Sholihah, Nikmatus; Mustain, Mustain; Hidayatin, Alfi Nur; Syaifudin, Mokhamad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study explores the integration of Artificial Intelligence (AI) and ChatGPT into Islamic Religious Education (PAI) as a response to the demands of 21st century learning. Using a qualitative library research approach, data were gathered from books, journal articles, and other scholarly sources, and analyzed through descriptive and interpretive methods. The findings show that AI, particularly ChatGPT, can strengthen students’ understanding of Qur’an, Hadith, Fiqh, and Akhlak, while also promoting greater engagement, motivation, and critical thinking. The adaptive and interactive nature of AI encourages active participation, supports personalized learning, and facilitates the internalization of Islamic values when guided by educators. These results suggest that AI-based media have considerable potential to enhance the quality of PAI instruction by bridging technological innovation with value-based education. The study concludes that AI can serve as an effective and innovative complement to traditional teaching methods, offering both pedagogical benefits and practical insights for the advancement of Islamic education.